The Social Impacts of Information and Communication Technology in Nigeria - Ogbuabor, Jonathan E.; Agu, Monica N.; Kalu, Ugbor I. (International Journal of Economics and Financial Issues, 2017)
This paper highlights the main types of information and communication technologies (ICT) used in Nigeria, the challenges of using them, and provides an indepth study of the social impacts of ICTs in Nigeria. We find that while some of these impacts are beneficial, like improvements in education, health, innovations, government service delivery, and participatory democracy; others are pervasively detrimental to the society as a whole, like e-fraud, hacking, dissemination of offensive images by foreign and local media, and job displacements leading to unemployment. Overall, we find that there is still a large scope of social benefits of ICTs yet to be explored in Nigeria. Keywords: information and Communication Technology; Social Impact; innovation; e-government; Nigeria JEL Classifications: O30; I00; O31; H11; N17